Application of Nonlocal Bars in Tension to Nanotechnology - Tepe, Aysegul; Artan, Reha (American Scientific Publishers, 2009)
In this work, a nonlocal bar in tension is studied in a nanometer length scale. By using the constitutive equation presented by Eringen in nonlocal elasticity, the inverse of the constitutive equation is derived and the extension of a sample bar is investigated. The differential equation is solved to illustrate the importance of nonlocal effects and compared with the classical elasticity solution. The results indicate that for tension bars in small length scales, nonlocal effects would have significant influences in the study of nano-structures and nonlocal theory could potentially play a useful role in analysis related to nanotechnology applications.